The Effect Of Various Sanitizing Agents On The Economics Of Hatching Kuttanad Duck Eggs - S., Harikrishnan; K, Narayanankutty; Chacko, Binoj; P. , Anitha (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
An experiment was conducted to evaluate the economics of various sanitizing agents for hatching eggs of Kuttand ducks (Anas platyrhynchos domesticus). A total of 2400 hatching eggs in four groups with 600 eggs in each group over a period of six weeks was collected for the study. The selected eggs were randomly allotted to the various cleaning methods (dry cleaning, luke warm water wash, glutaraldehyde wash and sodium hypochlorite wash) and the calculations were made on the basis of cost involved in washing/cleaning of eggs, percentage of hatchability and cost of day old ducklings. The findings of the present study revealed that the highest net return was obtained for dry cleaning of eggs, which indicated that egg without washing is more beneficial and profitable.